Corpus Callosum Integrity Relates to Improvement of Upper-Extremity Function Following Intensive Rehabilitation in Children With Unilateral Spastic Cerebral Palsy. (June 2021) - Robert, Maxime T.; Gutterman, Jennifer; Ferre, Claudio L.; Chin, Karen; Brandao, Marina B.; Gordon, Andrew M.; Friel, Kathleen
Background: The corpus callosum (CC) plays an important role in upper extremity (UE) function. The impact on UE function in children with unilateral spastic cerebral palsy (USCP) and improvements following intensive interventions remain unknown. Objectives: To examine the (1) relationship between UE function and CC integrity and (2) relationship between CC integrity and changes in UE function following intensive interventions. Methods: We retrospectively analyzed clinical and neuroimaging data from a sample of convenience of 44 participants (age 9.40 ± 3.10 years) from 2 larger trials. Participants received 90 hours of Hand-Arm Bimanual Intensive Therapy (HABIT) or Constraint-Induced Movement Therapy (CIMT). Unimanual dexterity (Jebsen-Taylor Test of Hand Function [JTTHF]) and bimanual performance (Assisting Hand Assessment [AHA]) were assessed preintervention and postintervention. CC tractography was reconstructed with diffusion tensor imaging (DTI) and segmented into 3 regions (genu, midbody, splenium). Pearson correlations and regression were used to assess the relationship between outcomes and DTI parameters (ie, fractional anisotropy [FA], number of streamlines, and mean, radial, and axial diffusivity). Results: Both groups improved in bimanual performance ( P < .01). The CIMT group improved in unimanual dexterity ( P < .01). Baseline unimanual dexterity and bimanual performance correlated with FA and number of streamlines for most CC regions ( P < .05). Following CIMT, pre-post changes in JTTHF were negatively correlated with axial and radial diffusivity of the CC, and AHA with splenium and number of streamlines for the CC, midbody, and splenium (all P < .05). Following HABIT, midbody FA was positively correlated with pre-post AHA changes ( r = 0.417; P = .042). Conclusions: CC integrity is important for UE function in children with USCP.